Appendix 1S: Complete dataset with viral Blastn hits from rectal and nasal swabs collected from semi-domesticated and wild Eurasian tundra reindeer (Rangifer tarandus tarandus) in Sweden, Norway, Finland, Iceland and Russia in different geographical locations and during two separate sampling periods. - Sánchez Romano, Javier; Omazic, Anna; Leijon, Mikael; Hagström, Åsa; Tryland, Morten; Kantanen, Juha; Reilas, Tiila; Rockström, Ulrika; Fedorov, Valery; Albhin, Ann (Zenodo, 2021)
Dataset with viral Blastn hits from rectal and nasal swabs collected from semi-domesticated Eurasian tundra reindeer ( Rangifer tarandus tarandus ) in Sweden (Regions A, B, C), Norway (Regions A, B, C), Finland (Regions A, B, C) and Yakutia, Russia (Regions A, B, C) and wild Eurasian tundra reindeer from all hunting areas in Iceland during two separate sampling periods.